Myoelectric signs of fatigue during constant and rhytmic isometric contractions - Felici, F.; Fattorini, L.; Filligoi, G. C.; Sbriccoli, P.; Bazzuchhi, I.; Rosponi, A. (International Journal of Computer Science in Sport, 2002)
In many sport activities (gymnastic, weight lifting, sailing, climbing etc) isometric or quasiisometric contractions endured until exhaustion are often requested. During isometric contractions the surface electromyographic signal (sEMG) exhibits amplitude and frequency content changes, which reflect central and peripheral modifications of the neuromuscular system (Farina, Fosci & Merletti., 2002). In skilled weight lifters these changes are paralleled by a rhythmic burst-like activity related to force fluctuations during fatiguing isometric contractions, possibly due to motor unit (MU) synchronization (Felici, 2001a). Recently, "non linear" tools have been introduced to quantify the presence of regular i.e., deterministic, structures within the sEMG and the recurrence quantification analysis (RQA) by means of its parameter (the percent of determinism - %DET) was shown particularly promising. This approach was tested by means of a sEMG modelling simulation (Farina et al., 2002) and confirmed on real data (Felici, 2002b). The present work was aimed at investigating the effects of two different muscle activation patterns on myoelectric signs of fatigue and on the deterministic behaviour of the sEMG. We believe that contractions involving MU recruitment/de-recruitment should affect the sEMG spectral content changes. Moreover, this kind of exercise could better detect the sensitivity of RQA to the presence of synchronization within the sEMG.